INTERAKTIVITAS RADIO SUARA SURABAYA: PENGGUNAAN, FUNGSI, DAN MODEL INTERAKTIVITAS - Budhi Widi Astuti; Bonardo Marulitua Aritonang (Jurnal Riset Komunikasi (JURKOM), 2019)
Radio Suara Surabaya (SS FM) is a private broadcasting institution capable of carrying out its role as a public radio. The uniqueness of its role begins with the switch of the SS FM function which originally dominated the content with entertainment into information content. This change in the dominance of content results in a two-way broadcast format, where there is interactivity in it. This study aims to find out about the interactivity that exists between SS FM and its listeners, including the media used, the forms of interactivity, and the factors of interactivity. Computer-Mediated Communication is one of the media theories used as a knife for analysis. Through qualitative research methods, it was found that in interactivity with the listeners, SS FM has standard rules that must be adhered to together. While the elements contained in it are participation, control and activity. In addition, the interactivity media used are telephone, online media and social media. Then the form of interactivity that occurs is interactivity of content and personal interactivity. While three factors cause listeners to interact actively with SS FM, namely the need for information, the need for self-actualization, and the need for self-existence.